2016
DOI: 10.1016/j.jconhyd.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and micellar solubilization of NAPL contaminants in aquifer rocks

Abstract: Surfactant-enhanced aquifer remediation is often performed to overcome the capillary forces that keep residual NAPL phases trapped within contaminated aquifers. The surfactant selection and displacement mechanism usually depend on the nature of NAPL constituents. For example, micellar solubilization is often used to cleanup DNAPLs from aquifers whereas mobilization is desirable in aquifers contaminated by LNAPLs. Although the majority of crude oils are LNAPLs, they often contain heavy organic macromolecules su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…The best washing formulation F1, comprised of 20% foamate and 2% Dehydol LS7TH in water, could form Type I microemulsion with polyolefin (near the transition region between Type I and Type III). The high TPH removal efficiency by Type I microemulsion might be due to the super-solubilization effect, where the swollen micelles incorporate a large amount of oil into their hydrophobic core (Tongcumpou et al, 2003;Javanbakht and Goual, 2016). The same trend was found in the study by Wu et al (2000), who reported that the microemulsion Type I (near the Type I to III boundary) and Type III had similar oil solubilization capacities.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The best washing formulation F1, comprised of 20% foamate and 2% Dehydol LS7TH in water, could form Type I microemulsion with polyolefin (near the transition region between Type I and Type III). The high TPH removal efficiency by Type I microemulsion might be due to the super-solubilization effect, where the swollen micelles incorporate a large amount of oil into their hydrophobic core (Tongcumpou et al, 2003;Javanbakht and Goual, 2016). The same trend was found in the study by Wu et al (2000), who reported that the microemulsion Type I (near the Type I to III boundary) and Type III had similar oil solubilization capacities.…”
Section: Discussionsupporting
confidence: 70%
“…Another potential washing agent is a surfactant-based microemulsion, which can be formulated by mixing different surfactants in water or saline water and is based on the experimental phase behavior of a surfactant-oil-water system (Winsor Type region). The removal of petroleum usually occurs via two mechanisms: solubilization via a Winsor Type I microemulsion and mobilization via a Winsor Type III microemulsion ( Javanbakht and Goual, 2016 ). Microemulsion-based washing agents can be achieved with a low surfactant amount; thus, the application of microemulsions could reduce the potential risk of new contaminants being released into the environment and ensure the economic practicality of the washing process ( Arpornpong et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the aging process, asphaltene molecules adsorbed on the rock surfaces, altering their wettability. 4 Since adsorption is a kinetic process, wettability alteration is a function of aging time. After 7 days of aging, the contact angles became almost constant, indicating that a minimum of one week was needed to alter the wettability of these substrates, as shown in the top curves of Figure 4.…”
Section: Effect Of Aging Timementioning
confidence: 99%
“…3 Surfactants with an intermediate hydrophile-lipophile balance (HLB) number favor the mobilization and, to a lower extent, the solubilization of oil in porous media. 4 Mobilization in this case manifests by the in-situ formation of bi-continuous Winsor Type III microemulsions, consisting of bilayer vesicles in equilibrium with oil and water phases. 5 A major limitation of surfactant flooding is the chemical losses encountered within the first few inches of the formation due to adsorption on minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Javanbakht and Goual demonstrated that environmentally friendly, nonionic surfactants are an effective means of mobilizing as well as solubilizing oil based-NAPLs. 21 Imbibition tests indicated that the trapped oil was mobilized and solubilized in a ratio of approximately 6:1, indicating that solubilization does indeed play a role in the removal of contaminants. Edwards et al showed that the amount of solubilization of polycyclic aromatic hydrocarbons into the aqueous phase was linearly related to the concentration of nonionic surfactant, with more solubilization at higher concentrations.…”
Section: Introductionmentioning
confidence: 97%